Big visual data analysis : scene classification and geometric labeling /: scene classification and geometric labeling. (2016) - (Computer vision scientist), Chen, Chen; Ren, Yuzhuo; Kuo, C.-C. Jay (Chung-Chieh Jay)
No abstract available